Fisher's "The Making of Index Numbers" - Young, Allyn A. (Quarterly Journal of Economics, 1923)
Journal Article Fisher's “The Making of Index Numbers” Get access Allyn A. Young Allyn A. Young Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 37, Issue 2, February 1923, Pages 342–364, https://doi.org/10.2307/1883934 Published: 01 February 1923